PRIMA 2019 : principles and practice of multi-agent systems : 22nd International Conference, Turin, Italy, October 28-31, 2019, Proceedings /: principles and practice of multi-agent systems : 22nd International Conference, Turin, Italy, October 28-31, 2019, Proceedings. (2019) - Unknown
No abstract available